Pendidikan Islam Dan Politik - Abdul Mujib; Yuyun Yunita (Pascasarjana IAIN Metro, 2018)
Education is a fundamental part of human need which must be fulfilled by every human being. Education is part of the political problem as the management of people's affairs) based on the ideology of the state. Based on a fundamental understanding, the politics of education of a country is determined by the ideology of the country. It is this factor that determines the character and typology of the society it establishes. Thus, the politics of education can be understood as an educational strategy designed by the state in an effort to create the quality of human resources) which is aspired. Similarly with Islam; will build a society in accordance with ideological ideals. The model of society it creates will of course be different from the society formed by the State ideology system. Through this observation of the ideological characteristics, the educational system traces that take place will be easily understood. The secular-capitalist education system gave birth to a secular education strategy so that in turn it would create a typology of a secular-capitalist society. Similarly, socialism and Islamic education system.